Evolution of mechanical performance and particle breakage in rubber-modified calcareous sand under low-frequency cyclic loading - Junli Gao; Yingmiao Zhou; Feiyu Liu; Zhen Zhang; Zili Dai; Xueyang Zhan (Bulletin of Engineering Geology and the Environment, 2026)

Abnormal resting-state functional connectivity in anhedonia: A systematic review and meta-analysis - Xuezhen Zhang; Xinyan Rong; Shiying Wang; Chengfeng Chen; Bin Zhang (Brain Imaging and Behavior, 2026)

Correction: Cullin 3 overexpression inhibits lung cancer metastasis and is associated with survival of lung adenocarcinoma - Jiayu Zhou; Shizhen Zhang; Yong Xu; Weiwen Ye; Zhijun Li; Zhoumiao Chen; He Zhengfu (Clinical & Experimental Metastasis, 2026)

Disease-induced changes in Ganoderma lucidum microbiome co-occurrence patterns and assembly processes - Zhixiang Han; Wenkang Yan; Yujian Yang; Antonino Malacrinò; Xingyue Wang; Weiwen Li; Zhen Zhang; Hongmiao Wu (Applied Soil Ecology, 2026)

Toxicological Insights Into Multiple Pesticide Exposures in Red Swamp Crayfish ( Procambarus clarkii ): Molecular Mechanisms, Risk Assessments, and Future Perspectives for Aquaculture - Dan‐Dan Bian; Zi‐Yi Xing; Shuang‐Gui Dai; Xiang Lu; Dai‐Zhen Zhang; Bo‐Ping Tang; Bao‐Jian Zhu; Qiu‐Ning Liu (Reviews in Aquaculture, 2026)
The rice–crayfish integrated system (RCIS) is vital to Asian aquaculture, yet its sustainability is threatened by a critical paradox: pesticides used in rice cultivation jeopardize the health of the red swamp crayfish ( Procambarus clarkii ) and the safety of its products. This review systematically synthesizes evidence establishing oxidative stress as the central hub linking pesticide exposure to multilevel toxicity in P. clarkii . We delineate how pesticides dysregulate key pathways (PI3K/AKT/mTOR, MAPK, NF‐κB), triggering apoptosis, metabolic disruption, and immunosuppression. A pivotal mechanism involves pesticide‐induced gut microbiota dysbiosis, which diminishes beneficial short‐chain fatty acids and enriches pathogens, thereby amplifying intestinal barrier damage and host vulnerability. These interconnected processes collectively stunt growth and heighten susceptibility to pathogens like white spot syndrome virus (WSSV). Beyond organismal effects, we evaluate environmental pesticide fate and propose a novel risk assessment framework integrating these sublethal endpoints. Our proposed mitigation strategies include eco‐friendly pesticides, ecological engineering, and microbiome‐directed interventions. We advocate for future research prioritizing multi‐omics and mixture toxicity assessment. By deciphering this toxicity cascade and translating insights into practice, this review aims to protect the productivity, ecological integrity, and food safety of integrated aquaculture systems for long‐term sustainability.

Stress Nutrition in Aquatic Animals: From Definition to Practice - Jian Zhang; Qianwen Ding; Ruobing Lou; Yuanpei Zhang; Yuanyuan Yao; Yalin Yang; Zhen Zhang; Chao Ran; Zhigang Zhou (Reviews in Aquaculture, 2026)
Aquaculture faces numerous challenges, with stress being one of the major issues that lead to growth loss, metabolic disorders, weakened immunity, redox imbalance, and organ damage in aquatic animals. Nutritional intervention is one of the effective strategies to address these problems. Traditional research has primarily focused on the impacts of a single stressor on specific aspects of particular aquatic animal species. However, in practical scenarios, aquatic animals are often simultaneously exposed to multiple, overlapping stressors. Thus, it becomes crucial to investigate the specific role of nutrients in anti‐stress and to consider their synergistic effects when used in combination. Nevertheless, some nutrients have overlapping functions or differences in the degree of treatment. Thus, it is necessary to synthesize the existing nutritional research on stress alleviation in order to provide more precise and economical nutritional strategies. This paper reviews the research progress in stress nutrition in aquatic animals, including the classification of stressors, stress response processes and their combined effects, as well as the development of nutritional strategies offering new perspectives for managing stress in aquaculture. It defines stress nutrition from the perspective of essential nutrients, conditional essential nutrients, and homeostasis regulation of gut microbiota, emphasizing the dynamic adjustment of nutritional requirements in response to various stressors. Additionally, it also provides an in‐depth discussion of the research progress, challenges, and future prospects in this field. Continued exploration in this field will reduce stress‐associated losses in aquaculture and promote the efficiency of food supply by this important agricultural sector.

Cover Image - Jian Zhang; Qianwen Ding; Ruobing Lou; Yuanpei Zhang; Yuanyuan Yao; Yalin Yang; Zhen Zhang; Chao Ran; Zhigang Zhou (Reviews in Aquaculture, 2026)
The cover image is based on the article Stress Nutrition in Aquatic Animals: From Definition to Practice by Zhigang Zhou et al., https://doi.org/10.1111/raq.70091 . image

Nitrogen-salt interaction in Pennisetum giganteum: Effects on soil, rhizosphere, and ion transport processes - Peng Wang; Chen Zhang; Kok Sin Woon; Wenyu Li; Xu Pei; Mengxue Liu; Kun Zhang; Wenyan Li; Junkang Guo; Zhen Zhang; Yongtao Li (Applied Soil Ecology, 2025)

A variational framework for inverse modeling: Case study in CO₂ sequestration - Zhen Zhang; Xupeng He (Advances in Water Resources, 2025)

Nitrite Toxicity in Shrimp Aquaculture: Mechanisms, Health Impacts, and Sustainable Mitigation Strategies - Dan‐Dan Bian; Yan‐Xia Shi; Xue Zhang; Xin Liu; Jun‐Jie Jiang; Xi‐Rong Zhu; Dai‐Zhen Zhang; Qiu‐Ning Liu; Bao‐Jian Zhu; Bo‐Ping Tang (Reviews in Aquaculture, 2025)
The rapid expansion of intensive aquaculture systems has caused escalating environmental challenges due to excessive nitrogenous waste accumulation, which surpasses the metabolic capacity of aquatic microbiota and elevates nitrite concentrations. As a pervasive environmental toxin, nitrite induces oxidative stress, disrupts metabolic homeostasis, and compromises gut microbiota and immune function in shrimp, leading to mass mortality, economic losses, and ecological disruption. These impacts threaten both aquaculture productivity and ecological sustainability. This review synthesizes three decades of research to elucidate the multifactorial mechanisms of nitrite toxicity, including genotoxicity, apoptosis, growth impairment, and dysregulated cellular signaling pathways. Key findings highlight that nitrite overload impairs mitochondrial function, dysregulates apoptosis pathways, and interferes with growth and reproductive processes, thereby undermining shrimp development and reproduction. To address these challenges, the review evaluates emerging mitigation strategies such as antioxidant‐enriched feeds, probiotic modulation, and biofloc technology, which optimize nitrogen cycling, enhance detoxification capacity, restore microbial equilibrium, and improve survival rates in experimental trials. Unlike prior fragmented studies, this review integrates mechanistic insights into nitrite toxicity with scalable interventions, proposing a novel decision framework for system‐specific nitrite management. This framework offers actionable recommendations for policymakers and industry stakeholders to balance aquaculture productivity with ecological sustainability. By advancing the understanding of nitrite's ecotoxicological impacts, this review charts a path toward resilient and sustainable aquaculture systems, transforming mechanistic insights into preventive protocols and offering a holistic perspective on nitrite pollution control that reconciles economic objectives with ecological sustainability.

Cover Image - Qingshuang Zhang; Hongwei Yang; Tsegay Teame; Chao Ran; Yalin Yang; Yuanyuan Yao; Qianwen Ding; Shubin Liu; Shengkang Li; Zhen Zhang; Zhigang Zhou (Reviews in Aquaculture, 2024)
The cover image is based on the Review Article Immune disorders induced by improper use of dietary immunostimulants in aquatic animals: Research progress and prospective solutions by targeting gut microbiota by Qingshuang Zhang and Hongwei Yang et al., https://doi.org/10.1111/raq.12852 . [Correction added on 27 March 2024, after first online publication: Cover image has been changed] image

Immune disorders induced by improper use of dietary immunostimulants in aquatic animals: Research progress and prospective solutions by targeting gut microbiota - Qingshuang Zhang; Hongwei Yang; Tsegay Teame; Chao Ran; Yalin Yang; Yuanyuan Yao; Qianwen Ding; Shubin Liu; Shengkang Li; Zhen Zhang; Zhigang Zhou (Reviews in Aquaculture, 2024)
Immunostimulants were widely used in aquafeed due to their multiple important functions, including promoting growth, enhancing non‐specific defence mechanisms and resisting infectious diseases. But the efficiencies of the positive effects of immunostimulants were affected by the duration of the administration and their dose. Short‐term and normal‐dose of immunostimulants promoted the growth and enhance non‐specific immunity of aquatic animals. However, improper use led to several immune disorders, including immune tolerance, immune exhaustion and over‐immunity. The application of two immunostimulant diets in rotation technique and the intermittent use of immune stimulant diets may solve the problems associated with immune disorders, but this application method will be limited by both species and immunostimulants. The occurrence of immune disorders is accompanied by different degrees of gut microbiota dysbiosis, especially significantly up‐regulated the abundance of Proteobacteria. Besides, the gut symbiotic microbiota plays a significant role in host immunity. Consequently, the regulation of gut microbiota may be an effective way to modulate immune disorders caused by improper use of polysaccharide immunostimulants. Regulating the gut microbiota not only solves the negative effects caused by improper use of immunostimulants without restrictions on both species and immunostimulants, but also has the advantage of simplicity and convenience compared to conventional approaches. In summary, this article reviews the possible negative effects caused by improper use of immunostimulants on aquatic animals and compares regular approaches with regulating gut microbiota. And gut microbiota maybe be used as a therapeutic target to improve immune disorders caused by immunostimulants in aquatic animals.

Attenuated cooling effects with increasing water-saving irrigation: Satellite evidence from Xinjiang, China - Chao Zhang; Jinwei Dong; Guoyong Leng; Russell Doughty; Kun Zhang; Songjun Han; Geli Zhang; Xuezhen Zhang; Quansheng Ge (Agricultural and Forest Meteorology, 2023)

Characterizing spatial, diurnal, and seasonal patterns of agricultural irrigation expansion-induced cooling in Northwest China from 2000 to 2020 - Chao Zhang; Quansheng Ge; Jinwei Dong; Xuezhen Zhang; Yan Li; Songjun Han (Agricultural and Forest Meteorology, 2023)

Advances of intra‐species molecular typing analysis of aquatic probiotics approved by the Chinese Ministry of Agriculture - Juan Hu; Yuanyuan Yao; Yalin Yang; Chenchen Gao; Fengli Zhang; Rui Xia; Chao Ran; Zhen Zhang; Jihong Liu Clarke; Zhigang Zhou (Reviews in Aquaculture, 2021)
Probiotics confer a health benefit on the host and could be used as a good alternative to antibiotics. Probiotics are strain‐specific when exerting their function, so it is necessary to identify them to strain level. In recent years, intra‐species molecular typing and identification methods have developed rapidly, which commonly are used for typing the main pathogenic bacteria and rare for studies on probiotic typing, whilst it is imperative. This article describes molecular typing methods including AFLP, RAPD, PFGE, ribotyping, MLST, rep‐PCR and whole‐genome sequencing to identity some aquatic probiotics approved by the Ministry of Agriculture of China, which are Bifidobacterium , Enterococcus , Lactobacillus , Pediococcus , Aspergillus , Bacillus , Rhodopseudomonas palustris and Streptococcus thermophilus . In addition, the principles, applications, advantages and disadvantages of these typing methods are also discussed.

Surface display system for probiotics and its application in aquaculture - Yuan‐Yuan Yao; Ya‐Lin Yang; Chen‐Chen Gao; Feng‐Li Zhang; Rui Xia; Dong Li; Juan Hu; Chao Ran; Zhen Zhang; Jihong Liu‐Clarke; Zhi‐Gang Zhou (Reviews in Aquaculture, 2020)
Aquaculture is a fast‐growing and rapidly expanding industry in the world. Probiotics are widely used in aquaculture and have provided benefits to aquatic animal health, and it is also a promising alternative to antibiotics for control of fish diseases. With the development of biotechnology, new expression systems and novel techniques for the surface display of heterologous proteins in surface of probiotics cells have been developed. This review provides an overview of the systems and strategies for displaying functional proteins on the surface of probiotics commonly used in aquaculture, which are Bacillus subtilis , Bacillus thuringiensis , lactic acid bacteria represented by Lactococcus lactis and yeast. Their applications in aquaculture especially for oral vaccine development afforded by this technology and prospects and challenges associated with this technology are also highlighted.